2018
DOI: 10.1007/s11069-018-3354-4
|View full text |Cite
|
Sign up to set email alerts
|

Surf zone hazards and injuries on beaches in SW France

Abstract: Surf zone injuries (SZIs) are common worldwide, yet limited data is available for many geographical regions, including Europe. This study provides the first preliminary overview of SZIs along approximately 230 km of hazardous surf beaches in SW France during the summer season. A total of 2523 SZIs over 186 sample days during the summers of 2007, 2009 and 2015 were analysed. Documented injury data included date and time; beach location; flag colour; outside/inside of the bathing zone; age, gender, country and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 53 publications
5
55
1
Order By: Relevance
“…The SW coast of France hosts 230 km of meso-macrotidal sandy beaches that are visited by millions of tourists each summer (Brumaud, 2016) and are considered to be surf beaches. Castelle et al (2018a) showed that along this stretch of coast, a large number of bather SZIs occur due to shore-break waves and channel rips, with a large number of additional SZIs sustained whilst surfing. The combination of large tide range and variable incident energetic wave climate and weather conditions result in complex and highly variable patterns of SZIs.…”
Section: 5% Of Leading Cause Of Rescue Inmentioning
confidence: 99%
See 3 more Smart Citations
“…The SW coast of France hosts 230 km of meso-macrotidal sandy beaches that are visited by millions of tourists each summer (Brumaud, 2016) and are considered to be surf beaches. Castelle et al (2018a) showed that along this stretch of coast, a large number of bather SZIs occur due to shore-break waves and channel rips, with a large number of additional SZIs sustained whilst surfing. The combination of large tide range and variable incident energetic wave climate and weather conditions result in complex and highly variable patterns of SZIs.…”
Section: 5% Of Leading Cause Of Rescue Inmentioning
confidence: 99%
“…Shorebreak waves are, on average, associated with a low proportion of surf zone rescues and injuries in most of existing studies (e.g. Australia (Brighton et al, 2013); 13% in UK (RNLI, 2017)), although higher proportions can be found (44.6% of the SZIs on the coarser grained and steeper beaches of SW France in Castelle et al, 2018a). More locally, shore-break waves were found to be responsible for over 82% of the SZIs at the steep beaches of Ocean City, Maryland (Muller, 2018).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Shorebreak waves are, on average, associated with a low proportion of surf zone rescues and injuries in most of existing studies (e.g. 8.5 % of leading cause of rescue in Australia, Brighton et al, 2013;13 % in UK, RNLI, 2017), although higher proportions can be found (44.6 % of the SZIs on the coarser-grained and steeper beaches of southwestern France in Castelle et al, 2018a). More locally, shore-break waves were found to be responsible for over 82 % of the SZIs on the steep beaches of Ocean City, Maryland (Muller, 2018).…”
mentioning
confidence: 95%